2021
DOI: 10.1021/acs.energyfuels.1c01544
|View full text |Cite
|
Sign up to set email alerts
|

Toward a More Comprehensive Understanding of the Kinetics of a Common Biomass-Derived Impurity: NH3 Oxidation by N2O in a Jet-Stirred Reactor

Abstract: Ammonia (NH 3 ) has garnered substantial attention in recent years due to its importance across many scientific and engineering domainsincluding its potential use as a carbon-free fuel and long-term energy storage option, its use in reducing combustion-generated nitrogen oxide emissions, its role as a decomposition fragment of many energetic materials, and its presence as an important impurity during biofuel and biomass combustion that can affect overall system kinetics, among others. Yet, it is generally rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The last paper in the group discussed the oxidation of ammonia. Here, Cornell et al performed experiments in a jet-stirred reactor, providing kinetic results for the ammonia reaction with N 2 O being used as the oxidizer instead of O 2 . They further pointed out the importance of the N 2 O + NH 2 = N 2 H 2 + NO reaction.…”
Section: Combustion Of Other Biofuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The last paper in the group discussed the oxidation of ammonia. Here, Cornell et al performed experiments in a jet-stirred reactor, providing kinetic results for the ammonia reaction with N 2 O being used as the oxidizer instead of O 2 . They further pointed out the importance of the N 2 O + NH 2 = N 2 H 2 + NO reaction.…”
Section: Combustion Of Other Biofuelsmentioning
confidence: 99%
“…The last paper in the group discussed the oxidation of ammonia. Here, Cornell et al 24 Six papers focused on the combustion of solid biomass. Three papers were interested in the reactivity of biochars.…”
Section: ■ Combustion Of Other Biofuelsmentioning
confidence: 99%
“…Recently, skeletal and reduced chemical mechanisms have been developed for ammonia/ n -heptane blends. , The combustion characteristics, including the IDTs and laminar burning velocities calculated using a homogeneous reactor, agreed well with the experimental results. However, gaps remain in our understanding of the kinetics of ammonia . Recently, numerical studies have been conducted on ammonia/diesel DF engines using the pilot injection of diesel. An increase in the ammonia substitution ratio (ASR) leads to higher unburnt ammonia and N 2 O emissions. , The N 2 O greenhouse gas effect has been approximately 300 times higher than that of carbon dioxide over a period of 100 years.…”
Section: Introductionmentioning
confidence: 99%
“…However, gaps remain in our understanding of the kinetics of ammonia. 21 Recently, numerical studies have been conducted on ammonia/diesel DF engines using the pilot injection of diesel. 22−25 An increase in the ammonia substitution ratio (ASR) leads to higher unburnt ammonia and N 2 O emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, despite its high ozone-depletion and global warming potential, the unique oxidizer N 2 O is being studied. , For instance, Parfenov et al delivered a new gas-phase selective oxidation of n-butenesraw materials for methyl ethyl ketonein the presence of N 2 O. Le Vaillant et al discovered a novel catalytic synthesis method for phenols, which are essential raw materials in the chemical industry, using N 2 O. Cornell et al reported a kinetic study of ammonia oxidation using N 2 O in a jet-stirred reactor, as ammonia is exclusively oxidized under conditions where N 2 O-rich O 2 oxidizers are present.…”
Section: Introductionmentioning
confidence: 99%